Multilevel Analysis of District- and City-Level Contextual Factors Influencing Hypertension Risk Among Adults: An Analysis of Indonesian Health Survey Year 2023 - Anindhita Saviorel Rivaldy; Bhisma Murti; Setyo Sri Raharjo; Vitri Widyaningsih; Eti Poncorini Pamungkasari (Journal of Epidemiology and Public Health, 2026)
Background: Hypertension remains a major public health challenge in Indonesia, with prevalence continuing to rise across different population groups. The burden of hypertension varies across settings, including urban and rural areas, socioeconomic levels, and regional contexts. This study aimed to examine how district- and city-level contextual factors influence the risk of hypertension among adults in Indonesia. Subjects and Method: A cross-sectional study included a sample of 48,878 adults who participated in the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia). The data were analyzed using multilevel multiple linear regression. Results: Multilevel analysis showed that the risk of hypertension increased among individuals aged ≥60 years (b= 4.12; 95% CI= 3.76 to 4.48; p < 0.001), compared with those aged <20 years. Senior high school or higher education (b= –0.40; 95% CI= –0.48 to –0.31; p <0.001) was associated with a lower risk of hypertension compared with individuals with no formal education. Higher BMI was associated with an increased risk of hypertension among individuals with BMI 18.5–25 kg/m² (b= 0.19; 95% CI= 0.09 to 0.30; p < 0.001) and BMI ≥25 kg/m² (b= 0.92; 95% CI= 0.82 to 1.03; p < 0.001). Female sex (b= 0.21; p < 0.001), urban residence (b= 0.06; p= 0.021), and high Gini Ratio (b = 0.17; p < 0.001) increased the risk of hypertension, whereas high physical activity and higher provincial minimum wage reduced the risk. The ICC of 0.37% indicated low variation across districts/cities. Conclusion: Hypertension risk among Indonesian adults is mainly driven by individual factors, while income inequality is the only contextual factor with a significant effect. These results emphasize the need for interventions targeting both personal health behaviors and socioeconomic disparities.